PENERAPAN STRATEGI INKUIRI PADA SUB POKOK BAHASAN KELILING DAN LUAS LINGKARANUNTUK MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR SISWAKELAS VIII SMP IT SYARIF HIDAYATULLAH SUKORAMBI TAHUN AJARAN 2012/2013 - Aliya, Vaidatul; Hobri, H; Sugiarti, Titik (Kadikma, 2014)
Abstract.Strategy of Inquiry learning are series of learning activity that emphasize on critical and analitycal thinking process to look for and find its own answer from the problems asked. This strategy can improve the students mind in learning and students achievement in the classroom. Steps of inquiryare orientation, formulating problem, formulating hypothesis, collecting data, testing hypothesis, and formulating conclusion. The result showed that teacher and students gave good responses toward teaching learning activity by using inquiry. Those good responses were proved by the improvement of studends learning activities. Students competence in material Circumference and Area of circle reached 74,42%. Beside that, there is good effect of the students though after teaching and learning process. All of them showed that inquirycan help students to look for and find the answer of problems are studied. Key Words : inquiry, students activities, achievement